First Contacts in Polynesia The Samoan Case (1722-1848) Western Misunderstandings about Sexuality and Divinity - Tcherk, Serge (ANU Press, 2008)
This book explores the first encounters between Samoans and Europeans up to the arrival of the missionaries, using all available sources for the years 1722 to the 1830s, paying special attention to the first encounter on land with the Lapérouse expedition. Many of the sources used are French, and some of difficult accessibility, and thus they have not previously been thoroughly examined by historians. Adding some Polynesian comparisons from beyond Samoa, and reconsidering the so-called 'Sahlins-Obeyesekere debate' about the fate of Captain Cook, 'First Contacts' in Polynesia advances a hypothesis about the contemporary interpretations made by the Polynesians of the nature of the Europeans, and about the actions that the Polynesians devised for this encounter: wrapping Europeans up in 'cloth' and presenting 'young girls' for 'sexual contact'. It also discusses how we can go back two centuries and attempt to reconstitute, even if only partially, the point of view of those who had to discover for themselves these Europeans whom they call 'Papalagi'. The book also contributes an additional dimension to the much-touted 'Mead-Freeman debate' which bears on the rules and values regulating adolescent sexuality in 'Samoan culture'. Scholars have long considered the pre-missionary times as a period in which freedom in sexuality for adolescents predominated. It appears now that this erroneous view emerged from a deep misinterpretation of Lapérouse's and Dumont d'Urville's narratives.